Weton: Reflections on Employee Interests to Become a Whistleblower - Purwanti, Lilik; Effendi, Soelchan Arief (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 18 No 1 (2023), 2023)
This study aims to reveal the employee's interest in reporting fraudulent acts in the Universitas Brawijaya Academic Business Entity and analyzes the employee's interest based on the weton . Informants include the director, deputy director, financial manager, treasurer, and administrative staff. This qualitative research was conducted through unstructured interviews as well as documentation methods to obtain information about weton from informants. This study found that some employees were interested and some were not. Whistleblowers with weton Rebo Pon , Akad Pahing , Sênin lêgi and Rêbo lêgi consider reporting fraud an obligation and a moral responsibility because it harms the organization. On the other hand, the whistleblowers with weton Kêmis pon and Sêtu kliwon feel uncomfortable, sorry, and afraid to report. The work environment and family form a character that encourages a person's interest in becoming a whistleblower. Keywords: weton, fraud, employee interest, whistleblower